The effect of 12 weeks of HIIT and curcumin consumption on oxidative indices in obese men with type-2 diabetes mellitus - Hasan Naghizadeh; Faeze Heydari (Shahid Beheshti University, 2022)
Background and Purpose: Considering that exercise and consumption of medicinal plants with antioxidant properties have a significant effect on the redox status of people with type-2 diabetes, it seems necessary to study the interactive effect of high-intensity interval training and curcumin consumption in people with type-2 diabetes. Therefore, the aim of this study was to evaluate the effect of 12 weeks of high-intensity intermittent exercise and curcumin consumption on oxidative indices in obese men with type-2 diabetes.Materials and Methods: In this quasi-experimental double-blind study performed with a pre-test and post-test design with a control group, 60 men with type-2 diabetes mellitus (mean age 38.76 ± 2.05 years, height 169.53 ± 2.81 cm, BMI 31.09 ± 1.56 kg/m2) randomly divided into four groups: HIIT, HIIT-curcumin, curcumin, and control.Exercise intervention three sessions per week (including 10 stages of training, each stage includes 30 seconds with an intensity of 80 to 85% HRR and 90 seconds of active rest with an intensity of 50 to 55% HRR) and taking 2100 mg of curcumin three times a day performed for 12 weeks. Sampling was performed in two stages, pre-test and post-test to measure the plasma concentrations of paraoxonase-1, superoxide dismutase, glutathione peroxidase and malondialdehyde. Data were analyzed using Shapiro-Wilk, one-way analysis of variance and two-way covariance method. The significance level was set at P < 0.05.Results: The results showed that the interactive effect of exercise and curcumin consumption significantly increased paraoxonase-1(P=0.014), superoxide dismutase (P=0.0001), glutathione peroxidase (P=0.023) and significantly reduced malondialdehyde (P=0.0001). Also, the effect of exercise alone significantly increased serum levels of paraoxonase-1 (P= 0.010), superoxide dismutase (P=0.002), glutathione peroxidase (P= 0.015) and malondialdehyde (P=0.0001) decreased. However, the effect of curcumin alone did not cause significant changes in serum levels of paraoxonase-1 (P= 0.053), superoxide dismutase (P=0.092), glutathione peroxidase (P= 0.055) and malondialdehyde (P=0.079). The highest significant increase from pretest to posttest in paraoxonase-1 (19.26%, P=0.0001), superoxide dismutase (18.37%, P=0.011), glutathione peroxidase (17.20%, P=0.0001) and the most significant decrease in malondialdehyde (24.47%, P=0.014) was observed in the exercise alone with curcumin group. The greatest effect on paraoxonase-1 (86%), superoxide dismutase (92%), glutathione peroxidase (81%) and malondialdehyde (88%) was the interactive effect of exercise and curcumin.Conclusion: The results of the present study showed that the effect of exercise alone is associated with significant changes in serum levels of antioxidant enzymes and malondialdehyde index. However, the effect of curcumin was not associated with significant changes. Finally, the main finding of the present study indicates that the interactive effect of exercise and curcumin, compared to the effect of each alone, is more suitable for improving the antioxidant and peroxidant activity of obese men with type-2 diabetes with hyperlipidemia.